Puss in boots - Rosie Greening (Berkhamsted, Hertfordshire, Make Believe Ideas, 2017)
A retelling of the story of Puss in boots in rhyming text Key sound short a spellings: a ; Secondary sounds: ck, oo, ss On cover: Includes rhyming activity, key words and picture dictionary